Exploring stakeholders' perceptions of the Triple Bottom Line in the UAE construction sector: A structural equation modeling approach - Sara Abdulmaksoud; Ayman Alzaatreh; Salwa Beheiry (Social Sciences and Humanities Open)
In 1994, John Elkington proposed the Triple Bottom Line (TBL) concept to assess and measure sustainability based on ecological quality, economic prosperity, and social equity. On a broad level, there is a solid understanding of the term sustainability and its TBL, however, when adopted in the construction sector, different stakeholders have different perceptions about the TBL of sustainability. None of the reviewed papers have considered analyzing the TBL of sustainability and how it impacts the stakeholders' perception of sustainability and their willingness to adopt sustainable construction measures in the UAE. Therefore, the aim of this research is to examine the relationship between the TBL of sustainability and subsequently evaluate stakeholders' perceptions of sustainability's environmental, economic, and social pillars within the UAE construction industry and assess their willingness to adopt sustainable practices. The literature was synthesized to design a survey, which was validated by the nominal group technique and gathered responses from 129 stakeholders in the construction sector, effectively capturing their perceptions of the TBL of sustainability. The responses were used to develop a theoretical model analyzed using Confirmatory Factor Analysis and Structural Equation Modeling. The findings revealed that stakeholders working in the UAE construction industry recognize the economic and social merits linked to environmental protection. Moreover, the favorable outcomes linked to the economic and social pillars positively influence stakeholders' perceptions and willingness to adopt sustainable practices in the construction industry.